2010
DOI: 10.1063/1.3527936
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of energy loss mechanisms in organic light-emitting diodes

Abstract: The external quantum efficiency of organic light-emitting diodes (OLEDs) is limited by several loss mechanisms. By applying a numerical model for the efficiency analysis of OLED devices, we analyze the distribution of the different energy loss mechanisms in bottom and top emission organic light-emitting diodes. We validate the findings by the comparison with experimental data measured on red state-of-the-art p-i-n devices containing the red phosphorescent emitting dye iridium(III)bis[2-methyldibenzo-(f, h)quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
249
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(255 citation statements)
references
References 10 publications
4
249
1
1
Order By: Relevance
“…The air mode exhibits two maxima at approximately 80 and 260 nm within the examined thickness range. This result is very similar to the results of previous calculations and simulations [12,14]. As shown in Fig.…”
Section: ~10supporting
confidence: 82%
“…The air mode exhibits two maxima at approximately 80 and 260 nm within the examined thickness range. This result is very similar to the results of previous calculations and simulations [12,14]. As shown in Fig.…”
Section: ~10supporting
confidence: 82%
“…optical wave guide (WG) modes, losses from absorption, and excitations of surface plasmon polariton (SPP) modes at metal interfaces. 18 Either the OLED suffers from large losses due to the SPP mode, which is excited at the metallic opaque back reflector, or, if the distance between organic emitter and the metal is increased, another WG mode as source of loss is introduced, while the SPP excitation is strongly reduced. 18 Typically, even though the experimentalist is free to ponder between different types of loss channels, known OLED layouts cannot exceed the limit mentioned above.…”
Section: 3-5mentioning
confidence: 99%
“…This enhances light outcoupling to some extent, even though it does not completely solve the problem of TIR. [10][11][12] Thomschke et al 13 demonstrated the lamination of a high refractive index microlens foil on top of a white OLED and obtained a device efficacy of over 30 lm/W (27% EQE). Recently, Kim et al achieved an EQE of 44.7% (1.8-fold enhancement) for a green top-emitting OLED using a microlens array that was fabricated by evaporating an organic capping layer through a shadow mask.…”
mentioning
confidence: 99%